Pengaruh Kualitas Produk dan Pemasaran Digital terhadap Keputusan Pembelian Pelanggan Kopi Arabika Provinsi DKI Jakarta dengan Harga sebagai Variabel Mediasi - Austin Natama; Ismail Razak; Guswandi (Jurnal Ekonomi dan Industri, 2025)
This study aims to analyze the influence of product quality and digital marketing on Arabica coffee purchasing decisions in Jakarta, with price as a mediating variable. The method used was a quantitative approach through a survey of 100 respondents, and data analysis using path analysis techniques. The results showed that product quality and digital marketing had a positive and significant effect on price and purchasing decisions. Price was also shown to have a positive influence on purchasing decisions and acted as a mediating variable between product quality and digital marketing on purchasing decisions. These findings suggest that improving quality and appropriate digital marketing strategies can encourage the formation of appropriate price values ​​and support increased purchasing decisions. Therefore, Arabica coffee business actors are advised to maintain product quality and optimize the use of digital channels in their marketing activities.